2013
DOI: 10.1021/ma400019m
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity, Segmental and Hydrogen Bond Dynamics, and Aging of Supramolecular Self-Healing Rubber

Abstract: In recent years, self-healing materials have attracted increasing attention due to their potentially spontaneous self-repairing ability after mechanical damage. Here, we focus on a supramolecular self-healing rubber based on fatty acids following the work of Leibler and co-workers. We study the heterogeneous network structure and hydrogen bond dynamics as well as its significant aging properties using several experimental techniques. NMR experiments reveal that the rubber is basically a two-component system, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 34 publications
1
57
0
Order By: Relevance
“…The rheological properties of the latter systems (i.e. type 2) have been thoroughly studied, in particular in the melt but with a strong emphasis on polymer chains that bear at least two stickers per chain, in order to allow for an efficient elastic behavior 12,13,14,15,16 . Many experimental and theoretical studies showed that in both cases the presence of these stickers strongly affects the rheological properties.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The rheological properties of the latter systems (i.e. type 2) have been thoroughly studied, in particular in the melt but with a strong emphasis on polymer chains that bear at least two stickers per chain, in order to allow for an efficient elastic behavior 12,13,14,15,16 . Many experimental and theoretical studies showed that in both cases the presence of these stickers strongly affects the rheological properties.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…36−44 In principle, molecular mobility can be deduced from simple FID signals where a fast or slow decay indicates the presence of rigid or mobile components, respectively. 45 In comparison, proton multiple quantum NMR (MQ NMR) mostly probes molecular motions that involve a large number of segments up to the level of the whole chain, which dominates the mechanical properties of soft polymeric systems. 39 Graf et al used 1 H MQ NMR under fast magic angle spinning (MAS) to elucidate the nature of the polymer segmental dynamics in polybutadiene 46 and cross-linked poly(styrene-co-butadiene) 47 melt far above the glass transition with site resolution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…39 Saalwachter et al introduced a reference signal by changing the phase cycling and were able to quantitatively analyze the segmental dynamics and structural constraints in polymeric soft materials utilizing Baum-Pines sequences 51 with a benchtop low-field NMR spectrometer. 39 45 Also, Litvinov et al utilized DQ NMR and T 2 relaxometry to study the rubber−filler interaction in carbon black and silica filled rubbers, and quantitative information about immobilization of rubber chains on the surface of fillers was obtained. 60−62 The segmental dynamics near clay surfaces had been hypothesized to play an important role in a new class of telechelic polybutadiene/clay nanocomposite physical gels.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Further investigations of Leibler's self-healing polymer by Sun, Saalwächter and coworkers showed that this material can be regarded as a nanophase segregated system [71]. The fatty acid chains form a minor mobile phase that accounts for 15% of the total sample.…”
Section: Hydrogen-bonded Polymersmentioning
confidence: 99%